Kualitas Pelayanan Pasien BPJS di Rumah Sakit - Raina Dwi Miswara; Samodra Wibawa (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2019)
Public services have become an important issue in Indonesia for more than a decade. One of them is health services, which is one of the basic needs whose provision must be held by the government as mandated in Article 28 H of the Constitution. For this reason, the Social Insurance Administration Organization (Badan Penyelenggara Jaminan Sosial, BPJS) was established on 1 January 2014. Are services to patients covered by BPJS satisfiying enough? This paper answers this question through literature studies and observations, comparing four hospitals in Java and two outside Java. It was found that there were still many problems in this service, and the most prominent was the queuing system that was unsatisfactory and too few staff and medical personnel and rooms compared to the increasing number of BPJS patients. In order to maintain public trust, the government needs to resolve this problem immediately